Food And Nutrition Status Of Households With Women Living With HIV In Uganda - Nakakawa, Frances; Mugisha, Johnny; Diiro, Gracious M.; Kaaya, Archeleo N.; Tumwesigye, Nazarious M. (Scientific African, 2020)
This study utilised a national dataset collected from women living with HIV/AIDS in Uganda to understand the Food and Nutrition Security (FNS) status among their households. Descriptive analytical methods were employed to characterise the households in relation to selected domains of FNS- access and utilization. Overall, results indicate that majority (69.3%) of the women in the sample had a normal BMI which could imply good food utilization and thus good FNS and; 22.1% were above the normal range, which could imply they were overweight. However, this may not be entirely true as one could have a normal BMI but have a “hidden hunger” which relates to micronutrient deficiencies. Given the status of the women under study especially those on antiretroviral drugs side effects of weight gain may be experience which could be misconceived as “good nutrition”. Female headed households were reported to be more vulnerable to FNS given the registered low dietary and higher shares of food expenditure on incomes. Similarly, households in the central and western regions reported better physical food access but poor economic food access while the reverse was true for the households in the Northern region. Ironically, urban households registered a low food insecurity in relation to share of food expenditure. As such, it is recommended that intervention strategies for improving food and nutrition security among vulnerable groups should not be a “blanket” or uniform but some categories should be given priority; for instance, HIV+ headed households and urban households.
Keywords: Food and nutrition security; HDDS; HIV; Uganda